2018
DOI: 10.1007/s40656-018-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenylbutazone (Bute, PBZ, EPZ): one drug across two species

Abstract: In this article we explore the different trajectories of this one drug, phenylbutazone, across two species, humans and horses in the period 1950–2000. The essay begins by following the introduction of the drug into human medicine in the early 1950s. It promised to be a less costly alternative to cortisone, one of the “wonder drugs” of the era, in the treatment of rheumatic conditions. Both drugs appeared to offer symptomatic relief rather than a cure, and did so with the risk of side effects, which with phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…134 Other studies on the development of methods for the detection of NSAID for doping practices in horses included the detection of ketoprofen in urine by GC-MS 135 and in plasma by high performance liquid chromatography-ultraviolet (HPLC-UV) detection, 136 pranoprofen enantiomers in plasma and urine by LC-MS, 137 indomethacin in urine by HPLC-UV, 138 tolfenamic acid in plasma by GC-MS, 139 fenoprofen in urine and plasma by GC-MS, 140 tolmetin in urine and plasma by HPLC-UV and LC-MS, 141 phenylbutazone and its main metabolite oxyphenbutazone in plasma by LC-MS, 142 phenylbutazone in urine and plasma by GC-MS, 143 piroxicam and tenoxicam in urine by LC-MS, 144 and salicylic acid in urine by LC-MS. 145 Owing to the widespread use of phenylbutazone in veterinary context, several previous reviews pointed out its possible use as doping agent in racehorses. [146][147][148][149] There are some examples of the development of broad-spectrum methods for the simultaneous detection of different NSAID drugs in equine urine, 150 plasma, 151 and feces 31 by both GC-MS 31,150 and LC-MS. 151 A group of NSAID that have grown in relevance in clinical practice for acute and chronic pain are the second-generation cyclooxygenase 2 (COX-2) inhibitors. Several papers presented methodologies for the detection of COX-2 inhibitors such as firocoxib 152 and celecoxib 153 in equine plasma by LC-MS.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…134 Other studies on the development of methods for the detection of NSAID for doping practices in horses included the detection of ketoprofen in urine by GC-MS 135 and in plasma by high performance liquid chromatography-ultraviolet (HPLC-UV) detection, 136 pranoprofen enantiomers in plasma and urine by LC-MS, 137 indomethacin in urine by HPLC-UV, 138 tolfenamic acid in plasma by GC-MS, 139 fenoprofen in urine and plasma by GC-MS, 140 tolmetin in urine and plasma by HPLC-UV and LC-MS, 141 phenylbutazone and its main metabolite oxyphenbutazone in plasma by LC-MS, 142 phenylbutazone in urine and plasma by GC-MS, 143 piroxicam and tenoxicam in urine by LC-MS, 144 and salicylic acid in urine by LC-MS. 145 Owing to the widespread use of phenylbutazone in veterinary context, several previous reviews pointed out its possible use as doping agent in racehorses. [146][147][148][149] There are some examples of the development of broad-spectrum methods for the simultaneous detection of different NSAID drugs in equine urine, 150 plasma, 151 and feces 31 by both GC-MS 31,150 and LC-MS. 151 A group of NSAID that have grown in relevance in clinical practice for acute and chronic pain are the second-generation cyclooxygenase 2 (COX-2) inhibitors. Several papers presented methodologies for the detection of COX-2 inhibitors such as firocoxib 152 and celecoxib 153 in equine plasma by LC-MS.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Sometimes, organismal features were made comparable by shifts in social values. In the case of twentieth-century pharmaceutical use in both horses and humans, as Worboys and Toon ( 2018 ) recount, biomedical comparisons between the two species became valid only after their relative social status shifted: In the mid-century, clinical observations of drug side-effects in horses and humans were not comparable, as horses were considered possessions rather than patients; but by the end of the century, the status of horses had changed, and increasing concern for their long-term health made potential health effects of drug use in humans and horses newly comparable. The shifting social value of nonhuman animals can also be seen in the paper by Dam et al ( 2018 ).…”
Section: Practising Comparisonmentioning
confidence: 99%
“…Likewise, Worboys and Toon ( 2018 ) argue for the importance of context in their comparison of the use of the anti-inflammatory drug phenylbutazone, or “bute,” in horses and humans through the last half of the twentieth century. For humans, the long-term risks inherent in the use of bute created an unstable clinical picture from the drug’s introduction in the 1950s; by the 1980s, it had fallen into disrepute and was banned.…”
Section: Papers In the “Working Across Species” Topical Collectionmentioning
confidence: 99%
“…David Cantor (1992) showed that British rheumatologists were unanimous that cortisone’s value had to be seen against the other therapies that they used and with which there continued to be innovations. The most promising new drug was Butazolidin (phenylbutazone), launched by Geigy as a specific for rheumatic diseases in 1951 (Worboys and Toon 2018). Phenylbutazone (or ‘bute’ as it was sometimes called) was an effective analgesic, but rheumatologists disagreed about its anti-inflammatory action and there were reports of severe side-effects (Hart and Johnson 1952).…”
Section: Cortisonementioning
confidence: 99%